Exploring the Roles and Function of Police Search and Rescue Teams in Canadian Agencies. (2nd June 2021) - Ferguson, Lorna; Gaub, Janne E; Huey, Laura
Abstract: Police search and rescue (SAR) teams play a vital part in the successful location of lost and missing persons; however, they remain an understudied policing component. Therefore, the purpose of this study is to improve and deepen scholarly knowledge of the police SAR aspects of missing persons cases. Specifically, this article aims to provide first insights into the roles and function of SAR teams in Canadian police services. With this research, we can begin to formulate a better understanding of their utility in police missing persons work. Through a thematic analysis of 34 in-depth, qualitative interviews with police SAR team members from 13 police services across Canada, we explore how SAR teams operate within police services and outline the varying roles police personnel comprise in these teams. Results reveal that police SAR teams operate with several distinct roles that have different functions within the larger police hierarchy. Furthermore, findings show that police SAR personnel are fulfilling a host of responsibilities in these teams while operating as a secondary duty, yet are called upon at any time and are required to respond immediately. These findings and their implications for police missing persons work are then discussed.